2003
DOI: 10.1046/j.1442-200x.2003.01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of antibiotic‐associated diarrhea in children by Clostridium butyricum MIYAIRI

Abstract: Clostridium butyricum MIYAIRI is effective for both the treatment and the prophylaxis of AAD in children, as it normalizes the intestinal flora disturbed by antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
163
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(167 citation statements)
references
References 7 publications
1
163
0
3
Order By: Relevance
“…It produces large quantities of short-chain fatty acids (SCFAs) (deVos et al, 2009), especially butyrate, and an active bacteriocin (Nakanishi & Tanaka, 2010); it also sporulates, allowing it to resist antibiotics that may disrupt other gut flora. It has previously shown effectiveness in the prophylaxis of CDAD in a mouse model (Kamiya et al, 1997) and in a clinical trial for prevention of antibiotic-associated diarrhoea in paediatric patients (Seki et al, 2003). In another clinical trial, CBM588 significantly reduced the incidence of detection of C. difficile toxin in the stools of patients taking Helicobacter pylori-eradication therapy (Imase et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It produces large quantities of short-chain fatty acids (SCFAs) (deVos et al, 2009), especially butyrate, and an active bacteriocin (Nakanishi & Tanaka, 2010); it also sporulates, allowing it to resist antibiotics that may disrupt other gut flora. It has previously shown effectiveness in the prophylaxis of CDAD in a mouse model (Kamiya et al, 1997) and in a clinical trial for prevention of antibiotic-associated diarrhoea in paediatric patients (Seki et al, 2003). In another clinical trial, CBM588 significantly reduced the incidence of detection of C. difficile toxin in the stools of patients taking Helicobacter pylori-eradication therapy (Imase et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Clostridium butyricum is a typical butyric acid-producing, spore-forming, gram-positive anaerobe, which is found in soil and in the intestines of healthy humans and animals. This C. butyricum is a probiotic bacteria used clinically to prevent disturbances of gastrointestinal microbiota, to treat diarrhea, to enhance humoral immune response and to promote digestion in humans (Ito et al, 1997;Seki et al, 2003;Isono et al, 2007). Our previous experiments demonstrated that fish oil diets reduced abdominal fat in broiler chickens, whereas C. butyricum supplementation increased intramuscular fat content in breast muscle (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Seki et al 36 investigated the behavior of the microbiota in the use of antimicrobials with or without the use of probiotics. They classified 110 children and teenagers between 1 month and 15 years of age, according to three groups: those who received only antimicrobial treatment, those who initiated the use of probiotics during antibiotic treatment, and those who combined probiotic and antimicrobial from the beginning of the treatment.…”
Section: Conflict Of Interest Referencesmentioning
confidence: 99%